Polluted River Water Treatment Via Pilot-Scale Membrane Photocatalytic Reactor (MPR) Incorporated Zno-Kaolin Under Different Light Intensity - Suhaimi, Mohammad Amirrul Hakim; Madon, Rais Hanizam; Hamdan, Mohamad Alif Hakimi; Hairom, Nur Hanis Hayati; Mohd Makhtar, Siti Nurfatin Nadhirah; Mohd Salleh, Zuliazura; Abd. Jalal, MZahar; Madon, Rais Mohd Hazri (Journal of Advanced Mechanical Engineering Applications, 2024)
Polluted river water treatment utilizes a mix of physical, chemical, and biological processes and activities. Conventional systems, including coagulation, flocculation, sedimentation, filtration, and disinfection, have several limitations. Hence, the Membrane Photocatalytic Reactor (MPR) is one of the most promising methods for polluted river water treatment. ZnO-Kaolin nanoparticles served as great photocatalysts for MPR performance. This study focuses on the pilot-scale hybrid MPR treatment of polluted river water under different light intensities (100, 125, and 225 watts) and irradiation times (20, 30, and 40 minutes). The treated water quality analysis is based on the Environmental Quality Act 1974 (EQA 1974). The kinetic rate was also investigated using pseudo-first-order and pseudo-second-order models. It was found that 225 watts and 30 minutes were the optimum values. The pilot scale hybrid MPR proved to fit well with the pseudo-second-order kinetic models, suggesting that the degradation follows a chemisorption mechanism. In conclusion, we believe the hybrid MPR pilot-scale system will enhance efficiency in cleaning dirty river water, all while meeting the standards of the EQA 1974.